The Effects of Expansive Shrubs on Plant Species Richness and Soils in Semi‐arid Communal Lands, South Africa. (10th July 2017) - Sholto‐Douglas, Craig; Shackleton, Charlie M.; Ruwanza, Sheunesu; Dold, Tony
Abstract: Expansion by expansive species can have severe ecological, social and economic impacts through the reduction of ecosystem goods and services and species richness. However, expansion by expansive species may also offer benefits to ecosystems and humans, through the supply of ecosystem goods and services (such as firewood, fodder and fruits), as well as potentially offering refugia in heavily used landscapes. Here, we examine the effects of four expansive dwarf shrub species ( Aspalathus subtingens, Dicerothamnus rhinocerotis, Pteronia incana and Oedera genistifolia ) on plant species richness (at the point scale), vegetation cover, soil properties and whether the expansive species offer refugia to other species. Plant species richness, cover and soil properties were recorded in 1‐m 2 quadrats located within a mosaic of expanded and non‐expanded patches for the four expansive shrub species. Plant species richness was significantly higher in the non‐expanded areas compared to the expanded ones for all four expansive species. Some of the expansive shrubs provided refugia to certain plant species and limited the frequency of other species. With regard to species composition, there was little separation of expanded and non‐expanded samples within sites, indicating that the site factors were stronger determinants of plant species richness and composition than expansion. Therefore, it is more likely that the reduction in species richness in expanded sites is caused by multiple drivers, including vegetation attributes cover, litter cover and soil nutrients (organic C, Zn and P) and soil compaction. Copyright © 2017 John Wiley & Sons, Ltd.